Infrared single photon detector based on optical up-converter at 1550 nm. Issue 1 (December 2017) - Bai, Peng; Zhang, Y.; Shen, W.
Abstract High performance single photon detector at the wavelength of 1550 nm has drawn wide attention and achieved vast improvement due to its significant application in quantum information, quantum key distribution, as well as cosmology. A novel infrared up-conversion single photon detector (USPD) at 1550 nm was proposed to work in free-running regime based on the InGaAs/ InP photodetector (PD)- GaAs/AlGaAs LED up-converter and Si single photon avalanche diode (SPAD). In contrast to conventional In0.53 Ga0.47 As SPAD, the USPD can suppress dark count rate and afterpulsing efficiently without sacrificing the photon detection efficiency (PDE). A high PDE of 45% can be achieved by optical adhesive coupling between up-converter and Si SPAD. Using a developed analytical model we gave a noise equivalent power of 1.39 × 10−18 WHz1/2 at 200 K for the USPD, which is better than that of InGaAs SPAD. This work provides a new single photon detection scheme for telecom band.